CFD MODEL OF LASER ADDITIVE MANUFACTURING PROCESS OF CYLINDERS - Tamsaout, Toufik; Kheloufi, Karim; Amara, El Hachemi; Arthur, Nana Kwamina; Pityana, Sisa (The South African Journal of Industrial Engineering, 2017)
A theoretical approach based on a numerical simulation using experimental data is proposed as a contribution to the study of laser-based additive manufacturing by direct energy deposition (DED). The aim is to simulate the stages of layer-by-layer build-ups by considering the induced generated liquid metal in a cylindrical geometry. For normal atmospheric conditions, a 3D model is developed using the finite volumes method to solve the governing equations of the occurring fluid flows and heat transfers. The model is based on the experimental work performed on the LENS system at the Council for Scientific and Industrial Research’s (CSIR) National Laser Centre (NLC), where Ti-6Al-4V cylindrical coupons are laser printed and characterised.